Macroeconomic Determinants of Tourism Demand in Malaysia: A Markov Switching Regression Approach - Soh, Ann-Ni; Puah, Chin-Hong; Jong, Meng-Chang (Business Management and Strategy, 2022)
A wave of studies has always surrounded the nexus of tourism development and economic growth in a nation. An assessment is provided in this study to examine the Malaysian tourism market dynamics. A series of macroeconomic variables has been utilised to model tourism demand and examine causal linkages among tourism and economic growth. Spanning from 2000 till 2018 on a monthly basis, the Markov regime switching regression provides an overview of tourism market performance and potential influences during recession and expansion periods of the Malaysian tourism cycle. Notably, the results present a reference chronology of the crises happening over the past two decades, the Granger causality of the variables, and different behavioural changes of the variables as well for both recession and expansion periods. Significant relationships have been revealed in this study that suggest that overall international tourism can drive economic growth and vice versa.